Differential in vivo activation of the class II and class III snRNA genes by the POU-specific domain of Oct-1. - Murphy, S (1997)
Many snRNA genes contain binding sites for the ubiquitous transcription factor Oct-1. In vitro studies have shown that this factor potentiates binding of an essential transcription factor (PTF) to the proximal sequence element (PSE) of snRNA genes, and activates transcription. Using Gal4 fusion proteins, I show here that the POU-specific region of the DNA-binding domain of Oct-1 is sufficient both to potentiate PTF binding in vitro and to transactivate pol II- and pol III-dependent snRNA genes in vivo . A single amino acid change in this domain abrogates both activation and interaction with PTF. The N- and C-terminal regions of Oct-1 also activate transcription of both classes of snRNA genes. Wild-type levels of Pol II-dependent U2 expression require all activation domains, whereas efficient activation of the pol III-dependent 7SK and U6 genes is effected by the POU-specific domain alone. These results indicate that contacts between PTF and amino acids in the POU-specific domain of Oct-1 are critical for efficient transactivation of snRNA genes in vivo. The POU-specific domain of Oct-2A also activates these genes, but the N- and C-terminal domains are relatively inactive.